دراسة أطياف زيت الزيتون في المنطقة الساحلية في سورية - خضرو, أحمد (Latakia University Journal -Basic Sciences Series, 2018)
يتناول هذا البحث الخواص الطيفية لزيت الزيتون المأخوذ من الساحل السوري. وغطى المجال الطيفي المرئي (360 - 800nm) وتصنيف العينات إلى مجموعات تبين وجود ثلاث مجموعات رئيسة. ولربط الخواص الطيفية مع جودة الزيت ومصدره الجغرافي تم قياس درجة حموضة العينات لتصنيفها وفق هذا المعيار فقط، ومن ثم مقارنة درجة الحموضة مع الخواص الطيفية والموقع الجغرافي (البعد عن الساحل، والارتفاع عن سطح البحر)، وقد تبين عدم وجود علاقة مباشرة بين جودة الزيت والموقع الجغرافي من جهة، ومع الخواص الطيفية في المجال المرئي من جهة أخرى. أجريت القياسات في المعهد العالي لعلوم الليزر وتطبيقاته – جامعة دمشق - سورية. The present work deals with the olive oil spectrum characteristics on the Syrian coast, and in the wave – length region (360-800 nm). We found from the analysis that there are three specific main groups of olive. To connect that spectrum characteristics with the olive goodness, and the geographical sources, we measured the specimens acidity according to these characteristics, then compared that with the sources (hight over the sea level, distance from the sea). The results proved that there is not any direct relation between olive goodness and the geographical places, and also the spectrum characteristics in the U.V. region The measurements were done in the high institute for Laser Sciences and its application – Damascus University – Syria.